THE ASSESSMENT OF PHYSICO-CHEMICAL AND BIOLOGICAL WATER QUALITY CHARACTERISTICS OF THE IBAI RIVER BETWEEN WET AND DRY SEASONS, KUALA TERENGGANU, MALAYSIA - Muhammad Barzani, Gasim; O. M. A., Laila; M. E., Toriman (2018)
The environmental study was carried to evaluate the condition of Ibai River, Kuala Terengganu, at East Coast of Peninsular. The objectives of this study are to determine physico-chemical, biological of water quality and classify them and to determine the spatial-temporal relationship based on one way ANOVA, regression and correlation analysis. 3 sampling stations were selected in this study to represent the water quality condition of the river. The 2005 to 2010 data of eleven water quality parameters: TSS, BOD, AN, COD, DO, TEMP, EC, SAL, TUR, NO3 and pH were analyzed. Under the statistical approach, all the calculations were done at 5% level of significant. The results show that most of stations were classified as slightly polluted (Class II) during dry season. During wet season, almost all stations were classified as moderate polluted (Class III) even at station 2 in 2009 were classified as polluted (Class V) due to very low WQI (24%).